Characterization of epithelial oral dysplasia in non-smokers: First steps towards precision medicine. (March 2018) - Rock, L.D.; Rosin, M.P.; Zhang, L.; Chan, B.; Shariati, B.; Laronde, D.M.
Highlights: The majority of patients with OED were smokers; yet NS with OED were at a higher risk of progression. OED in smokers and NS were similar in size and appearance, but differed with respect to site. NS with an OED at the FOM possessed a 38-fold increased risk of progression compared to smokers. LOH markers can identify high-risk lesions and are sensitive regardless of smoking risk habits. Abstract: Objectives: Tobacco usage is the strongest risk factor in the development of oral squamous cell carcinoma (OSCC), which mandates careful screening for oral cancers in smokers. However, there are indications that oral potentially malignant lesions, such as oral epithelial dysplasia (OED), in non-smokers (NS) have a higher cancer risk than those in smokers. Without tobacco as an etiology, the development of these lesions in NS may suggest genetic susceptibility. The increasing incidence of OSCC in NS calls for a better understanding of the natural history of OED in NS as compared to that of smokers. Materials and methods: Patients from a population-based longitudinal study with more than 10 years of follow up were analyzed. Of the 455 patients with primary OED (233 mild and 212 moderate dysplasia), 139 were NS and 306 were smokers. Demographic and habit information, clinical information (lesion site, size and appearance; toluidine blue and fluorescent visualization), microsatellite analysis for loss of heterozygosity (LOH) and outcome (progression) were compared between the two groups. Results and conclusions: The majority of patients with OED were smokers. Of these, more were males, non-Caucasians and heavy drinkers. A significantly higher number of OED in NS were in the tongue, whereas a significantly higher number of OED in smokers were in the floor of mouth (FOM). OED in NS showed a greater than 2-fold increase in cancer progression. Strikingly, OED located in the FOM in NS showed a 38-fold increase in cancer progression as compared to those in smokers.